2009
DOI: 10.1088/0964-1726/18/3/037003
|View full text |Cite
|
Sign up to set email alerts
|

Actuation displacement performance change of pre-stressed piezoelectric actuators attached to a flat surface

Abstract: Pre-stressed piezoelectric actuators such as RAINBOW, THUNDER™, and LIPCA have a curvature due to a mismatch of the coefficient of thermal expansion, which inevitably exists during the manufacturing process. This technical note provides an answer to the question of how their actuation displacement performance changes when the curved pre-stressed piezoelectric actuators are attached to a flat surface. Finite element analysis with the ANSYS™ program was used to calculate the stress distribution inside a LIPCA, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Furthermore, the resistance value r(t) on the WB changing as frequency of 2ω can be expressed as: (10) where ε(2ω) is the rate of detection resistance variation that contributes to the vibration amplitude at a frequency of 2ω and θ s is the vibrational phase shift.…”
Section: Self-actuating and Self-sensing Of Mems Cantilever Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the resistance value r(t) on the WB changing as frequency of 2ω can be expressed as: (10) where ε(2ω) is the rate of detection resistance variation that contributes to the vibration amplitude at a frequency of 2ω and θ s is the vibrational phase shift.…”
Section: Self-actuating and Self-sensing Of Mems Cantilever Sensorsmentioning
confidence: 99%
“…The choice of excitation mechanism by which the electrical energy is reciprocally converted to the mechanical vibration plays a critical role in the overall performance. The most commonly used excitation mechanisms are electrostatic [9], piezoelectric [10], and thermal actuations [11]. Moreover, several other energy conversion processes could be utilized to actuate vibrations in a cantilever sensor, such as electromagnetic Lorentz forces [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric strain constant, d, of the PZT generally depends on the compressive stress perpendicular to the polar axis (Krueger, 1967(Krueger, , 1968. With regard to a lightweight piezocomposite curved actuator, Goo et al (2009) concluded that the piezoelectric strain constant increases on account of the rise in lateral compressive stress during the curing process. They defined " d 31 À Á…”
Section: The Effect Of Residual Stress On the Piezoelectric Strain Constantmentioning
confidence: 99%
“…In order to calculate the changes in piezoelectric strain constants, we use the residual stress shown in Figures 57 and the dependence of the in-plane compressive stress on the piezoelectric strain constants shown in Figure 8. The change in the strain constant, Ád 3x can be calculated in the same manner as Goo et al (2009), from the equation:…”
Section: The Effect Of Residual Stress On the Piezoelectric Strain Constantmentioning
confidence: 99%
“…In this study, we assumed that the piezoelectric strain coefficient variations D d 31 and D d 32 , similar to those of Goo et al (2009), can be expressed as…”
Section: Nonlinear Piezoelectric Materials Propertiesmentioning
confidence: 99%